The Cold War in South Asia Britain, the United States and the Indian subcontinent, 1945-1965 - McGarr, Paul M. (Cambridge University Press, 2013)
This transnational history of the rise and fall of Anglo-American relations with India and Pakistan during the Cold War offers a new multidisciplinary perspective on the seminal post-independence period. Drawing on unpublished British, American, Indian and Soviet archival records it examines what benefits, if any, intervention conferred, and to whom.